(untitled) (REMUNOM, 2024)
The objective of this dissertation is to analyze the development of two autistic children, under the influence of the triad: family, school and therapies, in a school in the city of Linhares-ES. This interest stemmed from the problems encountered by educational monitoring, where the question was raised: how does the triad (family, school and therapy) influence the overall development of autistic children? Outlining as an investigative method to answer this question, we use a qualitative and exploratory approach to analyze the interphases of the proposed theme, analyzing the two children included in the municipal educational institution